PENGARUH KONSELING GESTALT DENGAN TEKNIK PERMAINAN DIALOG UNTUK MEMINIMALISIR SELF AGGRESION - Jayanti, Putu Rosma Dita; Suarni, NI Ketut; Dharsana, I Ketut (Jurnal Ilmiah Bimbingan Konseling Undiksha, 2018)
This study was done to know the effect of gestalt counseling by using dialogue game technique to minimize self-aggression of grade VIII students ofSMP Negeri 2 Singaraja, and to know the difference between the students who were given treatment and the students who were not. The population used by the researcher was grade VIIIof SMP N 2 Singaraja, The researcher took 2 study samples by using simple random samplingand determined that VIII 10 class as the experimental group and VIII 9 class as the control group in which each group had 25 students. The data collection methods in this study were observation, interview, diary, document recording and questionnaire of self-aggression pattern of Likert scale. In testing the first hypothesis, t-test was used and it was obtained that18,44> 1,710882; thus, it could be concluded that Gestalt counseling by using dialogue game technique had effects to minimize self-aggression of grade VIII students of SMP N 2 Singaraja. In addition, the second hypothesis found that2,506? 2,063. Therefore, it could be determined that the result of the study was significant. In other words, the hypothesis of the study was accepted. As a result, there were differences of self-aggression between grade VIII students that were given Gestalt counseling by using Dialogue Game Technique and the students that were not given Gestalt counseling by using Dialogue Game Technique.Keywords :Gestalt counseling, dialogue game technique, self-aggression